Retting of jute for quality fibre: constraints and solutions - Rajendra R, Chapke (Journal of Agricultural Extension Management, 2019)
This paper focuses on retting related constraints faced by farmers in the traditional method and on the improved method developed to address these constraints. The study revealed that more than 90 per cent of farmers were unaware about improved fibre extraction and retting technology of jute. Majority of them perceived that more labour was required for performing manual retting operation of jute with high wages of labour during the peak season followed by non-availability of good quality water and insufficient water bodies for retting. However, they did not care about getting quality jute fibre due to lack of grading systems in the markets, which resulted in less monetary gains. Promising retting technologies have been developed, which can address problems of jute growers by saving water, space, time, labour and ultimately the cost of production. Moreover, the farmers gave a positive response during the frontline demonstrations for implementation in their fields. There is an essential need to empower the farmers with the technological know-how through extension strategies such as conducting training and demonstrations for its wide adoption.